1992
DOI: 10.1002/ps.2780340303
|View full text |Cite
|
Sign up to set email alerts
|

Some physicochemical factors influencing foliar uptake enhancement of glyphosatemono(isopropylammonium) by polyoxyethylene surfactants

Abstract: Structure‐concentration–foliar uptake enhancement relationships between commercial polyoxyethylene primary aliphatic alcohol (A), nonylphenol (NP), primary aliphatic amine (AM) surfactants and the herbicide glyphosatemono(isopropylammonium) were studied in experiments with wheat (Triticum aestivum L.) and field bean (Vicia faba L.) plants growing under controlled‐environment conditions. Candidate surfactants had mean molar ethylene oxide (EO) contents ranging from 5 to 20 and were added at concentrations varyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 16 publications
4
53
0
4
Order By: Relevance
“…Estes produtos aumentam a hidratação da cutícula, incrementando a difusão de glyphosate através da mesma (Sherrick et aI., 1986;Gaskin & Holloway, 1992;de Ruitner & Meinen, 1998).…”
Section: Absorção E Translocaçãounclassified
“…Estes produtos aumentam a hidratação da cutícula, incrementando a difusão de glyphosate através da mesma (Sherrick et aI., 1986;Gaskin & Holloway, 1992;de Ruitner & Meinen, 1998).…”
Section: Absorção E Translocaçãounclassified
“…Cationic polyoxyethylene tertiary amine surfactants are more effective than nonionic surfactants at promoting glyphosate phytotoxicity (Wyrill and Bumside, 1977;Riechers, 1992). Although several studies have examined surfactant mode of action in promoting glyphosate phytotoxicity (O'Donovan et al, 1985;Sherrick et al, 1986aSherrick et al, , 1986bde Ruiter et al, 1988;Gaskin and Holloway, 1992;Rdyneberg et al, 1992;Stock et al, 1992), the precise mechanism(s) of surfactant interaction has not been deduced. Surfactants promoting greatest glyphosate phytotoxicity are required at higher concentrations than necessary for maximum reduction of the spray solution surface tension, indicating that their mode of action is not limited to increasing the spreading characteristics of the spray droplet (Sherrick et al, 1986b).…”
mentioning
confidence: 99%
“…The critical log KO, range has been defined as the range in which surfactant lipophilicity (based on EO content) does not strongly influence the uptake enhancement of compounds; its upper and lower limits may vary according to plant species (Stock et al, 1993). The contribution of the nitrogen atom to the hydrophilicity of ethoxylated alkylamines need not weaken greatly the influence of EO content as indicated in a previous study (Gaskin and Holloway, 1992). These authors demonstrated that reducing of the EO content of ethoxylated alkylamines to 5 or 10 mol reduced the surfactant-induced uptake of the polar compound glyphosate by field bean and wheat.…”
Section: Resultsmentioning
confidence: 99%